2020
DOI: 10.3390/plants9020156
|View full text |Cite
|
Sign up to set email alerts
|

Community Structure, Diversity and Potential of Endophytic Bacteria in the Primitive New Zealand Medicinal Plant Pseudowintera colorata

Abstract: Although the importance of the plant microbiome in commercial plant health has been well established, there are limited studies in native medicinal plants. Pseudowintera colorata (horopito) is a native New Zealand medicinal plant recognized for its antimicrobial properties. Denaturing gradient gel electrophoresis (DGGE) and Illumina MiSeq analysis of P. colorata plants from ten sites across New Zealand showed that tissue type strongly influenced the diversity and richness of endophytic bacteria (PERMANOVA, P &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 49 publications
3
14
0
Order By: Relevance
“…This was true for both bacterial and fungal endophytic microbiota (Table 1). These results corroborate with the study of Purushotham et al (2020) where the richness of endophytic Alpha, Beta, and Gammaproteobacteria was higher in leaves in comparison to stem and roots of primitive New Zealand medicinal plant Pseudowintera colorata. Fernandes et al (2015) and Sharma et al (2018) also observed higher diversity and greater species richness for fungal endophytes in leaf as compared to other plant tissues in Glycine max and Berberis aristata DC.…”
Section: Diversity Assessment Of Endophytessupporting
confidence: 90%
“…This was true for both bacterial and fungal endophytic microbiota (Table 1). These results corroborate with the study of Purushotham et al (2020) where the richness of endophytic Alpha, Beta, and Gammaproteobacteria was higher in leaves in comparison to stem and roots of primitive New Zealand medicinal plant Pseudowintera colorata. Fernandes et al (2015) and Sharma et al (2018) also observed higher diversity and greater species richness for fungal endophytes in leaf as compared to other plant tissues in Glycine max and Berberis aristata DC.…”
Section: Diversity Assessment Of Endophytessupporting
confidence: 90%
“…Among all, the strains of Bacillus, Pseudomonas and Cedecea exhibited the highest amounts of Psolubilization, siderophore, IAA, HCN, ammonia and lytic enzymes (chitinase, protease, and amylase). Earlier studies have also indicated that several Bacillus species isolated from medicinal plants produced phytohormones, solubilized P and improved growth of tomato (Abdelshafy Mohamad et al 2020) and Pseudowintera colorata (Purushotham et al 2020). Similarly, Pseudomonas species produced IAA and increased plant biomass of medicinal plant Astragalus mongholicus (Sun et al 2019).…”
Section: Discussionmentioning
confidence: 93%
“…The difference in numbers and types of carbohydrates and amino acids enriched in leaves and stems of sugarcane indicated that the variety B8 was stronger than ROC22, 10.3389/fmicb.2022.1000033 Frontiers in Microbiology 13 frontiersin.org and leaves were stronger stems. Changes in metabolites and metabolic pathways might the bacterial penetration in the root cell wall for their host (Purushotham et al, 2020) and decrease external N requirements. So, it was found that endophytic N-fixing bacteria has an essential role in carbon and N metabolism and improvement of sugarcane growth.…”
Section: Discussionmentioning
confidence: 99%